Southern resident killer whales and ecotourism - Soares, Sara (2010)
Tese de mestrado, Biologia (Biologia da Conservação), 2009, Universidade de Lisboa, Faculdade de Ciências On a global scale, there has been a rapid growth of the whale watching industry in the last decade. In 1998, a total of 87 countries was involved in commercial cetacean tourist activities, with more than nine million people participating (Hoyt 2001). Off San Juan Island, Washington, USA, southern resident killer whales (Orcinus orca) population is the key resource of the tourism industry. Due to its predictability and to the fact that it is readily found it became the main target of the industry, being watched nearly at a daily basis from May through September. A fleet of almost 80 vessels and over 500,000 people annually engage in whale watching in this region (Koski 2008). Recently, the southern resident population of killer whales experienced an almost 20% decline (Krahn et al. 2002), resulting in their listing as 'depleted' under the US Marine Mammal Protection Act (MMPA) and 'endangered' under the US Endangered Species Act (ESA) and the Canadian Species at Risk Act (SARA). This combination of intense tourism activity and a fragile population has unsurprisingly brought apprehensiveness and several attempts to assess the effects of tourism activities on marine mammals have been made. Recent studies have shown that vessel presence can have short-term behavioral impacts which may result in longterm impacts. This study examined vessels' density when whales are present in the west coast of San Juan Island, and the performance of surface active behaviors (SABs) by southern resident killer whales. The results show that over 70% of the vessels involved in this activity are at least at ½ mile from shore, when whales are travelling very close to shore. The performance of SABs was greater with fewer boats present. These results allowed the assessment of further measures to regulate vessels' traffic in this region. Resumo alargado em português disponível no documento